Reposisi Sketsa Dalam Pendidikan Desain Komunikasi Visual - Rahadian, Bambang Tri; Park, Johanes (Serat Rupa: Journal of Design, 2024)
Sketching is a technique conducted as the first phase of creating an artwork and design. As an activity that is carried out at the beginning of the creation, sketching activities are often overlooked and are considered not necessary to be stored or even appropriately mastered. This argument is based on the assumption that the main purpose of making artwork and design is only for the final result. This research traces back the important role of the sketching process in education in the Visual Communication Design Study Program (DKV). The method applied in this research is a descriptive qualitative method In the scope of phenomenological hermeneutics, which is a method to describe a natural or man-made situation or phenomenon. For providing a description, literature reviews, documentation, an interview, and observation into urban sketcher community members. Through this research, it can be presented that the Urban Sketcher Manifesto can be applied in sketch drawing materials within the scope of academic learning. The benefits of the Urban Sketcher Manifesto to students include the ability to capture dynamic atmospheres with perspective determination, observe the organic gestures of living creatures, practice drawing spontaneously, effectively, and efficiently, and become accustomed to annotating drawings and storytelling through sketches. The results of implementing the Urban Sketcher Manifesto in course materials for students include strength in lines, understanding of composition, the grasp of impressions rather than reality, and good coordination between mind and hand. In this research, sketching is repositioned as a process that cannot be ignored in the work of drawing illustrations or visual designs. In sketch drawings, the benefits can also be seen in various interactions experienced, such as interactions among fellow students, interactions with localresidents, interactions with the atmosphere of the location, and interactions with the observed objects. The result of the research is expected to engage discourses for up-to-date Visual Communication Design education